The Importance of Education as a Prevention of Vaping in Adolescents: A Scoping Review - Istianah Istianah; Misna Zakiyus Sabila; Jihan Nafisah Fauziyyah; Riswanti Septiani (Jurnal Manajemen Bisnis dan Kesehatan, 2026)
The aim of this study was to map relevant literature regarding the role of education in preventing vaping in adolescence. This study used a scoping review approach guided by the PRISMA-ScR guidelines. A systematic search was conducted on databases such as PubMed, Scopus, and Web of Science for English language articles published between 2014 - 2024. The study selection process was conducted in two stages by independent reviewers, followed by narrative data extraction and synthesis. These results are findings that suggest that education, often delivered by health care providers (doctors, nurses), through a variety of methods (e.g., counseling, online surveys, social media, virtual reality games, lectures), is consistently effective in increasing adolescents' knowledge about the dangers of vaping and changing their risk perceptions. Educational and counseling support in primary care settings has been shown to be an important component of prevention strategies. The conclusion is that education is a vital component in preventing vaping initiation in adolescents, contributing significantly to increasing health literacy and forming negative attitudes towards the product. However, further in-depth research is needed on the long-term impact of education on actual vaping behavior and the development of more specific interventions for high-risk populations. Implementation of evidence-based education programs is highly recommended to protect the health of the younger generation.